Sleeve Hymen as a Penetrate Problem in a Newly Married Woman: A Rare Case Report - Surya, Raymond; Aryasatiani, Ekarini (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2024)
Introduction: Imperforate hymen (IH), an uncommon congenital anomaly, is a failure to completely canalize the hymen. This report aims to describe a sleeve hymen in a newly married woman and the surgical approach to the patient.Case Illustration: A 24-year-old newly married woman came to the gynecology polyclinic complaining of difficulty in sexual intercourse in the last 6 months. She felt painful and hard penile penetration since the first time of sexual intercourse. Inspection of external genitalia showed there was a hymen covering all vaginal introitus without an erythematous surface. The diagnosis indicated that the patient had a sleeve hymen. The patient underwent a U-shaped incision far away from the urethra as a hymenectomy.Discussion: Most of the IH patients are asymptomatic until menarche. Excess of estrogen status can cause the thickening of the hymen, called the sleeve hymen or “redundant” hymen. Meanwhile, epithelial cells’ failure in the center of the hymen to degenerate or excess cell proliferation may cause a microperforate hymen. There are several choices of treatment for IH, including hymenectomy (cruciate incision or hymen excision), hymen-preserving surgeries (simple vertical incision and annular hymenotomy), carbon dioxide laser, or insertion of a Foley catheter.Conclusion: Good anamnesis and physical examination can lead to the correct diagnosis of sleeve hymen. Hymenectomy is one of the alternative treatments for married women who have less concern about hymen-preserving surgery.Penebalan Himen sebagai Gangguan Penetrasi pada Wanita Baru Menikah: Sebuah Laporan KasusAbstrakPendahuluan: Himen imperforata (HI) merupakan kelainan kongenital yang tidak lazim didefinisikan sebagai kegagalan dalam kanalisasi himen. Laporan ini bertujuan untuk menggambarkan penebalan himen pada wanita yang baru menikah dan pendekatan pembedahan kepada pasien.Ilustrasi Kasus: Seorang wanita baru menikah berusia 24 tahun datang ke poliklinik ginekologi mengeluh gangguan hubungan seksual sejak 6 bulan lalu. Dia merasa sulit untuk penetrasi dan nyeri sejak pertama kali berhubungan seksual. Inspeksi pada genitalia eksterna memperlihatkan terdapat himen yang menutupi seluruh introitus vagina tanpa permukaan eritema. Diagnosis pada pasien ialah penebalan himen. Wanita tersebut dilakukan insisi bentuk U menjauhi uretra sebagai himenektomi. Diskusi: Kebanyakan pasien HI asimptomatik sampai menars. Kelebihan estrogen dapat menyebabkan penebalan himen yang dikenal sebagai himen “tidak berguna”. Sementara itu, kegagalan sel epitel di tengah himen untuk degenerasi atau kelebihan proliferasi sel dapat menyebabkan himen mikroperforata. Beberapa pilihan tatalaksana pada HI, yaitu himenektomi (insisi krusiata atau eksisi himen), pembedahan dengan konservasi himen (insisi vertikal simple dan himenotomi anular), laser CO2, atau insersi kateter Foley.Kesimpulan: Anamnesis dan pemeriksaan fisik yang baik dapat membantu mendiaganosis penebalan himen dengan tepat. Himenektomi merupakan salah satu tatatalaksana alternatif untuk wanita yang sudah menikah.Kata kunci: himen imperforate; himenektomi; microperforate hymen; penebalan himen,